Impact of the UGT2B17 polymorphism on the steroid profile. Results of a crossover clinical trial in athletes submitted to testosterone administration - Martín-Escudero, Pilar; Muñoz-Guerra, Jesús A.; García-Tenorio, Soledad Vargas; Garde, Ester Serrano; Soldevilla-Navarro, Ana B.; Galindo-Canales, Mercedes; Prado, Nayade; Fuentes-Ferrer, Manuel E.; Fernández-Pérez, Cristina (Steroids, 2019)
•This study presents results of a triple-blind randomized placebo-controlled crossover trial in healthy athletes with a single dose of 250 mg of testosterone cypionate, the aim was to evaluate the impact of the influence of the UGT2B17 gen on the urinary steroid profile.•The testosterone and several main metabolites excretion are clearly affected by the UGT2B17 gen, especially for homozygous mutant (del/del) group.•The measurement of LH, and the analysis of CIMRS are very useful for those cases when the T administration will be no detected. This article studies the genetic influence of polymorphism of the UGT2B17 gen on the urinary steroid profile and its implications for the anti-doping field. The study presents the results of a triple-blind randomized placebo-controlled crossover trial with healthy athletes submitted to a single dose of 250 mg of testosterone cypionate. Forty urine samples were collected from each participant. Mass spectrometry-based techniques commonly used in Anti-Doping laboratories, were employed to measure the urinary concentration and the Δδ13C values of a selection of target compounds for testosterone (T) administration together with LH. Twelve volunteers were included in the study; the polymorphism was evenly distributed among them. After T administration, the most meaningful change affected the Testosterone/Epitestosterone ratio (T/E) and the urinary concentration of LH. In relation with T/E, the wild type homozygous (ins/ins) group there was a mean relative increase of 30 (CI 95%: 25.2 to 36.7); in the heterozygous mutant (del/ins) group it was 19.8 (CI 95%:15.9 to 24.7); and in the homozygous mutant (del/del) group it was 19.7 (CI 95% 14.9 to 26.2). In the case of LH, it́s observed how LH values decrease significantly after the administration of Testex homogeneously among the three groups. The main outcome was related to the (del/del) group (homozygous mutant), where due to the depressed basal level of the steroid profile, if the longitudinal steroid profile of the athlete was not available, the analysis by GC/MS would not produce an “atypical” result according to the WADA TD2016EAAS despite the T administration. However, the genotyping of the UGT2B17 polymorphism, the follow up of LH and the use of GC-C-IRMS makes it possible to identify most of these samples as Adverse.